Efeito do ácido indolbutírico e do ácido bórico no Enraizamento de miniestacas de vinhático - dos Santos, Esmael Matías Gomes; Tarnowski, Christian; Barroso, Deborah Guerra (Universidade Estadual do Norte Fluminense (UENF), 2024)
Poster